A Brief History of Incivility in Rural Postcolonial India: Caste, Religion, and Anthropology. (January 2018) - Simpson, Edward; Tilche, Alice; Sbriccoli, Tommaso; Jeffery, Patricia; Otten, Tina
Abstract: Anthropological studies of Indian villages conducted in the 1950s and 1960s form a valuable archive of rural life soon after India's independence. We compare sections of that archive with recent fieldwork in the same villages in Gujarat, Madhya Pradesh, and Odisha. If we trust the ethnography of the 1950s, domestic and caste spheres were the locations of village incivility. It is noteworthy that there is no reference in the early work to the Partition of the subcontinent that had occurred just a few years before. Neither is there mention of discrimination or violence carried out in the name of religion in these locations. New fieldwork reveals a different story about the rise of wholesale religious incivility in the public sphere. Caste has not vanished, but inter-caste relations have taken on new forms. We suggest that the intersection of affirmative action policies, political parties, and the systematic penetration of Hindu nationalist organizations has been crucial in the remaking of rural India.